Intellectual Capital Effect on Corporate Value with Productivity as a Moderation Variables in Banking Sector Companies Registered in Indonesia Stock Exchange for 2016-2019 - Badar Ilahi; Umi Muawanah; Oyong Lisa (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2021)
Firm value is the investor's perception of the company's success rate which is often associated with stock prices. The high share price will create high company value, so that trust will be able to increase confidence in the company's current and future performance.The research objectives are: i) to describe the effect of the components of intellectual capital (VAHU, VACA and STVA) on firm value in banking sector companies; ii) to describe the effect of the interaction of intellectual capital components (VAHU, VACA and STVA) with productivity on firm value in the banking sector.This research is a survey research using descriptive research type (explanatory research). The sample used is 37 companies from the banking sector listed on the IDX for the 2016-2019 period.The results showed that: (i) the components of the Intellectual Capital (IC) VAHU and VACA had no effect on firm value. (ii) The IC component (STVA) has a negative effect on firm value, so it is concluded that STVA does not have a significant effect on firm value and will in fact drive down firm value. (iii) The interaction between productivity and the VAHU and VACA variables has a positive and significant effect on firm value. (iv) The interaction between productivity and the STVA variable has no effect on firm value.